The Personal Communication Ability – Communication to Understand the Others (and Ourselves) - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
The success of human communication depends significantly on the communication skills of the individual. Just as a child develops from an instinctive being into a conscious being, learning countless things along the way, so we also can shape and develop our communication skills. This is important not only because it can contribute to a more successful personal and professional life, but also because it enables us to not only give and receive information, but also to share our feelings and needs more effectively. The aim of this chapter is to provide a brief overview of communication skills and then highlight the extent to which communication as a tool can help us to understand ourselves and the other party involved in the interaction, to articulate our own needs and interests more effectively.Keywords: personal communication skills, self-awareness, problem processing, neutralization methods, alternative conflict-resolution techniques